Influencers’ Credibility Dimensions: Attractiveness, Trustworthiness, and Expertise on the Purchase Intention in the Skincare Industry - Ananda, Putu Kirana Maharani Wika; Darma, Gede Sri (Universitas KH. Abdul Chalim Mojokerto, 2026)
The rapid growth of influencer marketing in the skincare e-commerce sector, particularly among Generation Z consumers in Bali, necessitates an investigation into the influence of influencers’ credibility dimensions, attractiveness, trustworthiness, and expertise, on purchase intention. This study aims to examine how these credibility factors, mediated by online customer engagement, affect purchase intention in Bali's e-commerce market. A quantitative approach was employed, utilizing a self-administered online questionnaire distributed to 170 respondents from Generation Z in Bali. Structural Equation Modeling (SEM) was applied to analyze the relationships between influencer credibility, engagement, and purchase intention. The findings reveal that attractiveness, trustworthiness, and expertise significantly influence purchase intention, with online engagement acting as a mediator. However, no significant moderating effects of engagement on the credibility-purchase intention link were found. These results underscore the importance of influencer engagement in enhancing the effectiveness of marketing strategies targeting Gen Z consumers. The study contributes to existing literature by extending theoretical models of influencer marketing and provides valuable insights for brands looking to optimize influencer partnerships in the skincare industry. These findings suggest that brands should focus on fostering strong online engagement with their audience to improve conversion rates and strengthen consumer trust.